Développement des collections documentaires «Découvertes» de Gallimard Jeunesse - une stratégie éditoriale à long terme - Wandel, Agnieszka (2022)
The main objective of this study is to reconstruct the long-term strategy of Gallimard Jeunesse, a major Frenchpublisher of books for children and youth, which has consisted of a constant planning, restructuring and revitalisationof more than a dozen collections and series published under the label of ‘Découvertes’ from 1983 until today. Thhistory of this wide-ranging project – one of the largest publishing project of the last decades – provides a pictureof the evolution of the publication model of contemporary non-fiction books for children. We will therefore focuson the size of the analysed collections, the evolution of their editorial form and texts – for example, the presenceand function of illustrations and/or auxiliary parts of the books – as well as the age of their readers, the relationshipbetween translations and French production, and international and inter-institutional co-publishing ventures.Presenting the most interesting and innovative examples of typographic and graphic solutions implemented by thepublisher will also provide important information, as these solutions have been widely imitated.
Keywords: non-fiction books for children and youth; French publishing market; children’s book typography; children’s book graphics; contemporary non-fiction book